Crecimiento débil - Sarmiento, Eduardo (Diario El Espectador, 2011)
De acuerdo con el reporte oficial, la economía creció 4,3% en el 2010. La cifra es una fracción de las proyecciones oficiales y corresponde al promedio de los últimos diez años. La composición del producto nacional refleja la estructura económica de los últimos veinte años y las prioridades no explícitas en el plan de desarrollo. La producción industrial creció 4,9% y si se le resta el aumento de las materias primas importadas, el valor agregado apenas llega a 3%, al tiempo que la agricultura continúo estancada en cero. La dinámica de la economía se origina en la minería y petróleo. El resto de la actividad proviene de los servicios que representan el 60% del producto nacional.

According to the official report, the economy grew 4.3% in 2010. The figure is a fraction of official projections and corresponds to the average of the last ten years. The composition of the national product reflects the economic structure of the last twenty years and the priorities not explicit in the development plan. Industrial production grew 4.9% and if the increase in imported raw materials is subtracted, the added value barely reaches 3%, while agriculture continued to stagnate at zero. The dynamics of the economy originate in mining and oil. The rest of the activity comes from services that represent 60% of the national product.
Keywords: Economía - Colombia; Desarrollo económico - Colombia; Productividad industrial - Colombia; Economy - Colombia; Economic development - Colombia; Industrial productivity - Colombia